Gender inequality in incivility: Everyone should be polite, but it is fine for some of us to be impolite - Chen-Xia, Xing J.; Betancor, Verónica; Chas, Alexandra; Rodríguez-Pérez, Armando (Frontiers in Psychology, 2022)
Civility is formed by social norms that guide our behavior and allow us to interact appropriately with others. These norms affect everyone and are learned through the socialization process. However, in the same process, people also learn gender norms that dictate how men and women should behave, leading to gender stereotypes and differentiated behavioral characteristics. The purpose of this research is to examine the relationship between gender and civility, and how we react to those who behave uncivilly given their gender. The results of Study 1 (N = 153) showed that even in a fictional and gender-neutral society, uncivil behaviors were associated with stereotypically masculine characteristics, and those who behaved uncivilly were dehumanized. In Study 2 (N = 144), gender differences were observed in incivility. Women were harsher when facing uncivil transgressors than men, especially if the transgressor was another woman. Our findings support the notion that gender norms are applied to civility, leading those supposedly equal social norms to unequal perceptions and evaluations.